Life insurance salespeople linking work stressors to proactive behaviors by passion: Servant leadership as a moderator - Weng, Aijun; Zhou, Lingjun; Sun, Fufu (Frontiers in Psychology, 2022)
As the main sales force of life insurance companies, salespeople have accounted for more than 50% of life insurance sales channels over the years, playing a pivotal role in the development of the industry. Since the adoption of the model of employment at an agency, the commission income of life insurance salespeople has largely relied on their sales volume, which requires employee proactivity under a great number of stressors. However, because previous studies have analyzed stressors in a single dimension, our understanding of the relationship between work stressors and proactive behaviors remains limited. Applying self-determination theory, we investigated differential relationships between challenge/hindrance stressors and proactive behaviors, which were expected to be mediated by passion and moderated by servant leadership. In the sample of 332 insurance salespeople, there was a positive (negative) relationship between challenge (hindrance) stressors and proactive behaviors. In addition, passion mediated the relationship between stressors and proactive behaviors, and servant leadership moderated the relationship between stressors and passion. Theoretical and practical implications are discussed.